Characteristics of symmetrical components for high impedance faults in distribution networks with photovoltaic inverters - Herris Yamashika; Syafii Syafii (Institute of Advanced Engineering and Science, 2024)
This work models a photovoltaic (PV) inverter connected to an IEC microgrid system. The purpose of this study was to find the characteristics of symmetrical components before and after a high impedance single phase short-circuit fault. The IEC microgrid system is tailored to the distribution system in Indonesia, where the applied voltage is 20 kV. Only parameters related to the short-circuit study are included in the model. A second-order generalized integrator frequency-locked-loop is utilized to represent the 3-phase PV inverter. The inverter model, previously treated as an ideal current source, and positive sequence current are no longer employed, as they fail to depict the characteristics of symmetric components during a phase-to-ground short-circuit fault. The IEC microgrid system connected to the PV inverter is simulated using ATPDraw-electro magnetic transient program (EMTP). Simulation results reveal that the changes in the symmetric component values of current after a fault experience a very insignificant increase. Meanwhile, the positive sequence voltage values following the short-circuit fault exhibit a negligible decrease. In contrast, the negative sequence and zero sequence voltage components after the short-circuit fault undergo a significant increase.